Right ventricular systolic function and associated anatomic risk factors in fetuses with transposition of the great arteries: Evaluation by velocity vector imaging - Lin, Shan; Cao, Haiyan; Hong, Liu; Song, Xiaoyan; Liu, Kun; Xie, Mingxing; Yang, Yali (Frontiers in Cardiovascular Medicine, 2023)
Objectives: The aim of this study was to evaluate right ventricular (RV) systolic function in fetuses with transposition of the great arteries (TGA) using velocity vector imaging (VVI), and to investigate the impact of different factors on RV systolic function in TGA fetuses. Methods: This was a retrospective cross-sectional study of fetuses referred to our tertiary center between 2015 and 2019. Maternal and fetal baseline characteristics, conventional echocardiographic and myocardial deformation indices were collected in fetuses with TGA at 20 to 28 weeks’ gestation, which were compared with normal fetuses with comparable gestational age (GA). RV deformational parameters including global and regional longitudinal peak systolic strain, strain rate and velocity were measured using off-line speckle tracking analysis. The univariate and multivariate linear regression analysis was established to evaluate the independent risk factors for RV global longitudinal systolic strain (RVGLSs) and strain rate (RVGLSRs). Results: In total, 78 fetuses with TGA (including 49 fetuses with complete transposition of the great arteries (d-TGA) and 29 fetuses with Taussig-Bing anomaly (TBA)) and 49 normal fetuses were included. Compared with normal controls, global and most regional RV longitudinal systolic peak velocity, strain and strain rate were lower in d-TGA and TBA fetuses (P < .05). Compared with normal controls, global and most regional RV longitudinal systolic strain were lower in d-TGA fetuses without PS and VSD, while RVGLSs and RVGLSRs were lower in TBA fetuses without PS. The VSD was an independent determinant of RVGLSRs (P=0.024) in d-TGA group. And PS was an independent determinant of RVGLSs and RVGLSRs (P=0.012, P=0.027) in TBA group. Conclusions: Early impairment of RV systolic function has already occurred in TGA fetuses during the 2nd trimester of pregnancy. PS, VSD and FO were independent risk factors for decreased RV function.